PENINGKATAN KEMAMPUAN MEMAHAMI CERITA FIKSI MELALUI BANTUAN MEDIA GAMBAR - Agussalim Waangsir (JSSHA ADPERTISI JOURNAL, 2021)
This class action research done to overcome the problem overcome the difficulty learn in improving ability read the the understanding of fiction story, hence one of solution which can grow and develop the ability of student of class of VI SD of Country of Mappala apriceaciation of fiction story needed an Activity strategy through draw media. In general this research target to increase ability of student of class of SD of Mappala comprehend the fiction story constructively draw media and improve the ability think the literal, inferensial, evaluative and apresiatif through media Applying draw in study read the understanding of fiction story. This research uses the research device qualitative class action. The result obtained from this research from cycle I know that (1) ability think the students as much 53 (17,84%) coalification very well to fourth of ability aspect think, (2) ability think as much 83 students (27,94%) coalification good to fourth of ability aspech think, (3) ability think the as much 199 much people (40,07%) coalification last for fourth ability aspect think, (4) ability think as much 32 people (10,77%) less to be fourth ability think, and (5) ability think the student as much 10 (3,36%) less once. Fromm this result coalification inferential that as much 18 people coalification average of last for fourth think ability. Ability think in doing duty: (1) ability think as much 56 students (18,85%) coalification very well to be fourth ability aspect think, (2) ability think as much 85 students (28,62%) coalification of good to fourth of ability aspect think, (3) ability think as much 124 students (41,75%) coalification of lass fourth coalification of ability aspect think, (4) ability think as much 25 people (8,41%) less to fourth of ability think, and (5) ability think the students as much 7 (2,35%).